Language at Stake in International Research Collaboration—Methodological Reflections on Team-Based and Time-Intensive Ethnography - Glasdam, Stinne; Jacobsen, Frode F.; Ågotnes, Gudmund; Stjernswärd, Sigrid (Qualitative Sociology Review, 2024)
Based on experiences from multiple international research projects, spanning several decades and utilizing various forms of collaborative ethnographic approaches, this article aims to reflect on challenges and potentials regarding language and communication when researching across jurisdictions. Thematically, the research projects that we draw on in this paper, are concerned with aging and healthcare, while the primary focus of the paper remains on the methodological implications of conducting international, collaborative, and time-intensive ethnography. Moreover, the aim is to contribute to enhancing researchers’ awareness of and preparedness to meet and address such challenges in future research endeavors. The article discusses how English often serves as a lingua franca for Western-dominated international research collaborations, having implications for researchers and study participants alike, as well as the use of interpreters and potential linguistic pitfalls. In the article, we argue that attention and reflection on language and communication in research are significant for how collaboration in research transpires, the opted methodical choices, and, ultimately, for research quality, while often being under-appreciated. International ethnographic fieldwork requires thorough preparation and reflection to properly handle linguistic and cultural competencies, nuances, and understandings incorporated in the researchers, with subsequent consequences for research processes and outcomes.